The Effect of Gas Evolution on Hydrodynamic Characteristics of Fluid Flow in Pipeline - Siginer, D (American Society of Mechanical Engineers, 2016)
A relative motion of different phases leads to formation of certain forces at the interface of transported fluid and pipe walls. In the non-isothermal flow case a thermal interaction between the phases will affect the flow velocity, the pressure and the temperature distributions in variable cross section pipes. Laboratory experiments were conducted in order to study the effects of the gas generation at the pipe walls on the hydrodynamic characteristics of the two-phase oil/gas flow. It is shown that a throughput capacity of the pipe is affected by the temperature difference between the oil and the pipe walls. At certain temperature difference value (∼3°C) the pipe capacity reached a maximum value. Copyright © 2016 by ASME.